2019
DOI: 10.1021/acs.langmuir.9b00543
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogen Bonds on the Dielectric Properties of Interfacial Water

Abstract: The dielectric constant for water is reduced under confinement. Although this phenomenon is well known, the underlying physical mechanism for the reduction is still in debate. In this work, we investigate the effect of the orientation of hydrogen bonds on the dielectric properties of confined water using molecular dynamics simulations. We find a reduced rotational diffusion coefficient for water molecules close to the solid surface. The reduced rotational diffusion arises due to the hindered rotation away from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 59 publications
9
79
0
Order By: Relevance
“…37 Water confined in reverse micelles, in cellulose nanocrystals, near surfaces or in the hydration sphere of the hydrophobic headgroups of tetramethylurea experiences a "stiffening" of its hydrogen bond network compared to bulk liquid water. [38][39][40][41][42][43][44][45] Reduction of the number and length of hydrogen bonds in confined water, initially detected by neutron scattering and confirmed by theoretical predictions, 42,[44][45][46][47] causes the dielectric constant of water to decrease, as shown by dielectric imaging. 35 These alterations are manifested even at relatively large length scales.…”
Section: Interaction Of Water With Surfacesmentioning
confidence: 67%
“…37 Water confined in reverse micelles, in cellulose nanocrystals, near surfaces or in the hydration sphere of the hydrophobic headgroups of tetramethylurea experiences a "stiffening" of its hydrogen bond network compared to bulk liquid water. [38][39][40][41][42][43][44][45] Reduction of the number and length of hydrogen bonds in confined water, initially detected by neutron scattering and confirmed by theoretical predictions, 42,[44][45][46][47] causes the dielectric constant of water to decrease, as shown by dielectric imaging. 35 These alterations are manifested even at relatively large length scales.…”
Section: Interaction Of Water With Surfacesmentioning
confidence: 67%
“…In X-ray absorption spectra of bulk sodium nitrite solutions measured by the Saykally group, no appreciable ion pairing was observed [32]. We note, however, that the lower dielectric constant at the air/water interface [33,34] will increase the propensity for ion pair formation. Simulations by Venkateshwaran et al have shown that ion pairing near the interface can be enthalpically and entropically favorable for oppositely charged ions, as it releases some hydrating waters to the bulk and reduces pinning of capillary waves [35].…”
mentioning
confidence: 63%
“…The method can also be used to define the demarcation interface between the pore and the protein in continuous theories of ion transport such as the Poisson-Nernst-Planck (PNP) theory [68]. The method can thus provide fundamental insights into the electrostatics and dynamics of ions in sub-nanopores, where the dielectric properties on the nanoscale remain a challenging unsolved problem and a subject of intensive research [35,36,69,70].…”
Section: Discussionmentioning
confidence: 99%